The Effect of Data-driven Learning & Image-schema-based Polysemy Networks Instruction on Learning Spatial Prepositions of Verticality: The Case of Moroccan EFL Learners - Nihal Bouabida (JURNAL ARBITRER, 2020)
This paper reports on a quasi-experimental study investigating the effects of a teaching methodology that combines Cognitive Linguistics (CL) and Corpus Linguistics (CrpL) insights on the acquisition of the two sets of English spatial prepositions of verticality, over/above and under/below. In addition, it is also concerned with learners’ attitudes towards the method of instruction. A total of 55 Moroccan first-year university students participated in this study, 22 of which were assigned to the experimental group, and 26 to the control group. The experimental group received what we termed the IPDDL instruction, which involves cognitive representations of the prepositions based on Image-schemas, the Principled Polysemy model, and Data-Driven Learning. The control group, in contrast, received a traditional instruction based on definitions and example sentences provided in dictionaries. Participants' performance was measured with pre-, post-, and delayed post-tests in the form of a semantic judgment task and a gap-filling task. The findings demonstrate that the IPDDL method of instruction was significantly more effective in helping students acquire vertical prepositions, and its advantages proved durable posterior to two weeks of the instruction period. Thus, this study lends support to the applicability of a CL-CrpL-inspired methodology in second language instruction.